Automated people movers and transit systems 2013 : half acentury of automated transit -- past, present, and future : proceedings of the Fourteenth International Conference, April 21-24, 2013, Phoenix, Arizona - International Conference on Automated People Movers (14th : 2013 : Phoenix, Ariz.); Leder, William H.; Sproule, William J., editor; Transportation & Development Institute (American Society of Civil Engineers) (Reston, Virginia : American Society of Civil Engineers, 2013)
Includes bibliographical references